2021
DOI: 10.3390/foods10123032
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Oxidative Stability and Sensory Properties of Frankfurter-Type Sausage as Influenced by the Addition of Carrot (Daucus carota) Paste

Abstract: This study examined the addition of carrot paste (CP) at levels of 3%, 5%, and 10% as a potential antioxidant in frankfurter-type sausages, denoted as F1, F2, and F3. F0, was a control sample with no addition of CP. All formulated samples were stored for 14 days during which their physicochemical, oxidative stability, and sensory properties were evaluated. Results showed that the pH of frankfurter-type sausages was not affected by the addition of CP, however, higher pH values were observed in CP-enriched sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 86 publications
4
13
0
Order By: Relevance
“…For instance: (i) a positive correlation was observed between the thiol level and the amount of the incorporated sesame flour in sausage samples, and (ii) the highest level of thiol level was found in samples belonging to the S2 batch containing the largest amount of sesame flour in their recipes. The results are in agreement with the findings of Sam et al 35 . who reported that the addition of carrot paste, rich in antioxidant sources, in the formulation of frankfurter‐type sausage improved their oxidative stability.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For instance: (i) a positive correlation was observed between the thiol level and the amount of the incorporated sesame flour in sausage samples, and (ii) the highest level of thiol level was found in samples belonging to the S2 batch containing the largest amount of sesame flour in their recipes. The results are in agreement with the findings of Sam et al 35 . who reported that the addition of carrot paste, rich in antioxidant sources, in the formulation of frankfurter‐type sausage improved their oxidative stability.…”
Section: Resultssupporting
confidence: 93%
“…For instance: (i) a positive correlation was observed between the thiol level and the amount of the incorporated sesame flour in sausage samples, and (ii) the highest level of thiol level was found in samples belonging to the S2 batch containing the largest amount of sesame flour in their recipes. The results are in agreement with the findings of Sam et al 35 who reported that the addition of carrot paste, rich in antioxidant sources, in the formulation of frankfurter-type sausage improved their oxidative stability. The degradation of myofibrillar and sarcoplasmic proteins on day 10 could be due to proteases such as Lactobacillus fermentum, which exhibited a certain degree of enzymatic activity on myofibrillar proteins; one explanation could arise from the fact that oxidation induced crosslinking throughout disulfide bonds, in agreement with the findings of Sun et al 36…”
Section: Electrophoretic Analysis Of Sausages During Fermentationsupporting
confidence: 93%
“…Alirezalu et al (2017) reported a decrease in the pH of frankfurter‐type sausages prepared with green tea, stinging nettle, or olive leaf extract. Furthermore, Sam et al (2021) reported a decrease in the pH during storage for frankfurter‐type sausage prepared with Daucus carota paste.…”
Section: Resultsmentioning
confidence: 99%
“…The highest moisture content was observed in the CC3 treatment, with 66.77% at week 1. Similarly, Sam et al (2021) reported that the addition of carrot paste to frankfurter-type sausages increased the moisture content due to the presence of fiber. Furthermore, over time, the moisture content in the samples decreased slightly due to physicochemical changes.…”
Section: Proximate Compositionmentioning
confidence: 88%
“…Total cholesterol levels as affected by different cooking methods revealed that grilled and roasted chicken nugget samples had significant (P<0.05) lower total cholesterol content (Sam et al, 2021) compared to fried chicken nuggets (Table 4). This agreed with that of Yun-Sang Choi et al (2010) where lower cholesterol content was obtained in Frankfurter samples containing rice bran with reduced fat.…”
Section: Quality Of Chicken Nugget Based On Total Cholesterolmentioning
confidence: 99%